The struggle of the Saki underground organization against the Nazi occupiers. 1942–1944 - V. A. Ivanov (Омский научный вестник: Серия "Общество. История. Современность")
In the article, based on both previously unknown and published documents, there is considered the history of the underground struggle of Valentin Vyacheslavovich Kamler in the territory of the city of Saki of the Crimean ASSR. The author used materials from: the funds of the State Archive of the Republic of Crimea, the archival department (municipal archive) of the administration of the city of Saki, the museum of local history and mud therapy of the city of Saki. The actions of the underground workers are analyzed, including the following aspects: anti-fascist propaganda and agitation; collection, manufacture and storage of ammunition, military equipment; intelligence activities; the attraction of personnel from Nazi-allied foreign military contingents to the side of the Soviet government. In this work for the first time since the end of the Great Patriotic War, the names of the provocateurs who extradited V. V. Kamler and his associates to the Nazi special services and the police, are named. The publication is addressed primarily to researchers of the underground resistance movement, local historians and publicists.